Ginsenoside F1 Ameliorates Endothelial Cell Inflammatory Injury and Prevents Atherosclerosis in Mice through A20-Mediated Suppression of NF-kB Signaling - Qin, Meng; Luo, Yun; Lu, Shan; Sun, Jing; Yang, Ke; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2017)
Atherosclerosis is a chronic inflammatory disease and endothelial cell injury is the initial event. In this study, we investigated the protective effects of ginsenoside F1 (GF1) on atherosclerosis and the potential molecular mechanisms of ox-LDL induced endothelial injury. ApoE-/- mice were fed a high fat diet and orally treated with GF1 (50 mg/kg/day) for 8 weeks. Atherosclerotic plaque and LOX-1, TLR4, NF-κB expression levels in the aortic root and inflammatory factor MPO in whole body were measured. The treatment with GF1 induced a remarkable reduction in the atherosclerotic lesion area, LOX-1, TLR4 expression and decreased the MPO distribution. Meanwhile, in vitro study, we confirmed that GF1 treatment greatly increased ox-LDL-injured endothelial cell viability, ameliorated LOX-1, TLR4 expression levels and reduced monocytes adhesion. Protein microarray demonstrated that GF1 significantly inhibited G-CSF, ICAM-1, MIP-1δ, IL-1α, IL-15, IL-16 levels. Mechanistically, the GF1 treatment suppressed the NF-κB nuclear translocation. Furthermore, our data indicated that GF1 significantly increased A20 expression level and A20 siRNA markedly abolished the attenuation of GF1 on NF-κB nuclear translocation and inflammatory factors expression. Our results suggest that the GF1 may be a potential drug for anti-atherosclerosis.